Intertemporal Distributive Judgement - Hirose, Iwao (Ethical theory and moral practice, 2005)
This paper considers the simple two-person two-period case of distributive judgement, and argues (a) that sensible intertemporal distributive principle should consider both the distribution of people's life time well-being and the distribution of people's well-being at each period and (b) that, if (a) is correct, Egalitarianism is more acceptable than Prioritarianism since the latter must choose either one.